Ultra-high photon flux high-harmonic generation - Tschernajew, Maxim; Hädrich, Steffen; Klas, Robert; Gebhardt, Martin; Horsten, Roland; Weerdenburg, Sven; Pyatchenkov, Sergey; Coene, Wim; Breitkopf, Sven; Herrfurth, Oliver; Rothhardt, Jan; Eidam, Tino; et al. (Optics InfoBase Conference Papers, 2022)
We present a highly stable, easy-to-use HHG source delivering a record photon flux of >1011 photons/s at 69eV-75eV, being tunable to approx. 100eV which will be used for future photon-hungry applications.
CRIS-Team Scopus Importer:2023-04-20